Repair of the axial dorsal skin flap in rats treated with ozonized oil - Nakamura, Aline Medeiros [UNESP]; da Costa, Marcelo Carrijo [UNESP]; Gómez, Jorge Luis Álvarez [UNESP]; de Paiva, Felipe Noleto [UNESP]; De Nardi, Andrigo Barboza [UNESP] (Medicina Veterinaria (UFRPE), 2023)
Axial pattern flap represents an important option in reconstructive surgery, consisting of an artery and a direct cutaneous vein at their base and allowing a large area of skin to form the flap to cover the wound. However, the technique can present complications, mostly necrosis due to vascular involvement. In this context, ozone therapy can be used to accelerate the healing process of poorly vascularized and contaminated wounds. The objective of this article was to evaluate the effects and repair of the dorsal axial flap in Wistar rats at the receiving bed, using treatment with high-peroxidation ozonized oil. The study was carried out with 18 rats, divided into two groups with 9 animals: GG group (common sunflower oil) and GO group (ozonized sunflower oil). During the experimental period, macroscopic and microscopic evaluations were carried out, in order to observe the healing and repair of the surgical wound. Data were submitted to statistical analysis. The cosmetic appearance on GO was significantly better than GG. Blood vessel count, hemorrhage and reepithelialization were significantly higher in GO when compared to GG, while the presence of necrosis did not differ between groups. The mean total area of the flaps between the groups was statistically different, higher in the flaps in GO. The results showed that the use of ozonized oil in an axial pattern flap results in a favorable appearance and better reepithelialization in the treated group.
Reparação do retalho axial dorsal em ratos tratados com óleo ozonizado
Keywords: angiogenesis; collagen; ozone therapy; reconstructive surgery